Michel Houellebecq, information management and our new dark age. (February 2020) - Williams, Russell
Rejecting readings that seek to celebrate the unique, creative voice of the literary author, this essay strives to describe an element of the deep cultural logic at work in Michel Houellebecq's fiction. To do so, the essay embraces and considers the appropriation, or what has been described as plagiarism, of Houellebecq's literary style, suggesting a relationship with the structure of feeling of the contemporary information age. Taking its starting point as Houellebecq's own former career in IT, it posits that his work can be read as both a symptom of, and a reaction to, the anxious information overload of contemporary society rather than only a continuation, or reactivation, of the realist novel. In doing so, it proposes a more comparative and conceptual approach to reading Houellebecq than perhaps the French studies community has done to date, and itself transgresses the tendency to read Houellebecq within the frame provided by the canonical, frequently nineteenth-century, French novel.